2006
DOI: 10.1038/sj.emboj.7601109
|View full text |Cite
|
Sign up to set email alerts
|

Repair deficient mice reveal mABH2 as the primary oxidative demethylase for repairing 1meA and 3meC lesions in DNA

Abstract: Two human homologs of the Escherichia coli AlkB protein, denoted hABH2 and hABH3, were recently shown to directly reverse 1-methyladenine (1meA) and 3-methylcytosine (3meC) damages in DNA. We demonstrate that mice lacking functional mABH2 or mABH3 genes, or both, are viable and without overt phenotypes. Neither were histopathological changes observed in the gene-targeted mice. However, in the absence of any exogenous exposure to methylating agents, mice lacking mABH2, but not mABH3 defective mice, accumulate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
192
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(208 citation statements)
references
References 43 publications
13
192
1
1
Order By: Relevance
“…Likewise, in vivo experiments in humans, such as examination of the effect of gene polymorphisms [6] and nutritional status [6,7] on DNA metabolism, have used labeled one-carbon donors to label monocyte DNA. Nucleoside hydrolysates of DNA also have been used in determining the base composition of DNA, including investigation of epigenetic modification such as deoxycytosine methylation [8,9], oxidative damage [10,11], or unique DNA composition [12].…”
mentioning
confidence: 99%
“…Likewise, in vivo experiments in humans, such as examination of the effect of gene polymorphisms [6] and nutritional status [6,7] on DNA metabolism, have used labeled one-carbon donors to label monocyte DNA. Nucleoside hydrolysates of DNA also have been used in determining the base composition of DNA, including investigation of epigenetic modification such as deoxycytosine methylation [8,9], oxidative damage [10,11], or unique DNA composition [12].…”
mentioning
confidence: 99%
“…Bioinformatics analysis has identified a family of nine different mammalian AlkB homologues (ALKBH), including the obesity-associated protein FTO 13,14 . Although in vitro repair activities have been observed for some ALKBH proteins 10,13,15,16 , only ALKBH2 has been firmly established as a repair enzyme 17 , and non-repair functions have also been proposed [18][19][20] . We and others recently showed that ALKBH8 contains a MT domain, which is the functional mammalian Trm9 homologue, and requires a small accessory protein, TRM112, for activity (Fig.…”
mentioning
confidence: 99%
“…A third one, FTO, has been recently shown to repair 3-meT in DNA, and it affects obesity in mammals through an unknown mechanism 17 . ABH2 acts as the primary housekeeping enzyme in mammals for repairing endogenously formed 1-meA lesions in duplex DNA 18 . The in vivo function of ABH3 is still unclear but it has been shown to repair base lesions in RNA as well as DNA 15 .…”
mentioning
confidence: 99%